Musical Cities - Adhitya, Sara (UCL Press, 2018)
Musical Cities represents an innovative approach to scholarly research and dissemination. A digital and interactive 'book', it explores the rhythms of our cities, and the role they play in our everyday urban lives, through the use of sound and music. Sara Adhitya first discusses why we should listen to urban rhythms in order to design more liveable and sustainable cities, before demonstrating how we can do so through various acoustic communication techniques. Using audio-visual examples, Musical Cities takes the 'listener' on an interactive journey, revealing how sound and music can be used to represent, compose, perform and interact with the city. Through case studies of urban projects developed in Paris, Perth, Venice and London, Adhitya demonstrates how the power of music, and the practice of listening, can help us to compose more accessible, inclusive, engaging, enjoyable, and ultimately more sustainable cities.